Introductory Microbiology - Gross, Trevor Faull, Jane Ketteridge, Steve (Chapman & Hall, 1995)
Written for diploma level students and those undertaking introductory courses or modules in microbiology as part of their degree course, this book aims to cover the fundamental principles of microbiology and their applications.